Bumiputera entrepreneurship : an evaluation of the entrepreneurship training programs conducted by Majlis Amanah Rakyat (MARA) and the Malaysian Entrepreneurship Development Center (MEDEC) - 255283 Norfadzillah Hitam (Honolulu : University of Hawaii, 1994)
Thesis (PhD) -- University of Hawaii, 1994